Measurement of fiber diameter and length of vicuna fiber obtained from community management in Jujuy province, Argentina - Takashima, Cecilia (2017)
This work presents results of objective measurements of vicuña fiber obtained from wild animals and community management in Jujuy Province, Argentina, from 2014 to 2015. The aim of this paper is to provide technical information to improve the method of shearing and fiber classification, and also describe the quality attributes of the vicuña fiber in this geographic region. Mean fiber diameter (MFD) and staple length (SL) were measured on three different sites of fleece. The influence of the animal sex, the method of shearing and the site of fleece were also studied. Results indicate that sex has not significant effect of measured parameters, although the sampling site of fleece has affected these fiber caracteristics. The method of shearing may be a significant contributor to staple length variation.